The Analysis of Consumptive Financing for Civil Servants at Bank Nagari Conventional and Sharia Bukittinggi - Wahyu, Sri; Ummul Khairi, Annisa; Oktavia, Aulia (Jurnal Locus Penelitian dan Pengabdian, 2024)
Consumer financing has become an essential product in the banking industry. Civil Servants (PNS) are one of the significant groups in the consumer financing market. The provision of consumer financing for PNS is not only available in conventional financial institutions but also increasingly prevalent in Islamic financial institutions. This study aims to analyze and compare the interest rate systems in conventional banks, namely sliding, flat, and annuity, with the interest rate system in Islamic banks, namely the declining margin annuity method applied by Bank Nagari in consumer financing. This research method uses a qualitative approach with in-depth interviews with PNS who are customers of Bank Nagari Syariah Bukittinggi and simulation data on the Bank Nagari Conventional website Calculator. Based on interest calculations, it is evident that the method with the least bank interest income is the sliding method at Bank Nagari Conventional, followed by the declining margin annuity method at Bank Nagari Syariah. Thus, this study provides valuable insights for PNS customers in choosing financing products that are beneficial to customers and align with their needs and values